mHealth Intervention for Dementia Prevention through lifestyle Optimisation (MIND-PRO) in a primary care setting: protocol for a randomised controlled trial in people with low SES and/or migration background - Edo Richard; Esther Van den Berg; Ron Handels; Henrike Galenkamp; Eric P Moll van Charante; Marieke P Hoevenaar-blom; Anne Roos van der Endt; Martien J H Kas (BMJ Open)
Introduction The Mobile Health (mHealth) Intervention for Dementia Prevention through lifestyle Optimisation (MIND-PRO) study addresses the increasing prevalence of dementia among populations with lower socio-economic status (SES) and/or a migration background. The study aims to evaluate the effectiveness and implementation of an mHealth intervention designed for self-managing lifestyle modifications with remote coaching to reduce dementia risk factors.Methods and analysis This prospective randomised open-label blinded end point (PROBE) trial follows a type 2 hybrid effectiveness-implementation design with a 12-month intervention period. It aims to recruit 692 participants in Dutch primary care. Entry criteria include age 50–75 years, low SES and/or migration background, one or more dementia risk factors (hypertension, dyslipidaemia, diabetes mellitus, physical inactivity, smoking, depression and overweight) or manifest cardiovascular disease and possession of a smartphone. Participants are randomised to a coach-supported, interactive app facilitating self-management of dementia risk factors or to a control app with static health information. The primary effectiveness outcome is a composite score of systolic blood pressure, non-high-density lipoprotein cholesterol and body mass index. Implementation outcomes include coverage, adoption, acceptability, appropriateness, feasibility, fidelity, costs and sustainability of the intervention. Secondary outcomes include the Cardiovascular Risk Factors, Ageing and Dementia risk score and its individual risk factors, and disability, physical activity, depressive symptoms, cognitive functioning and daily distance moved.Ethics and dissemination The MIND-PRO trial is funded by the Netherlands Organisation for Health Research and Development (ZonMw, grant number 10510032120004) and approved by the Ethics Committee of Amsterdam UMC (reference: METC 2023.0770). Results are expected in 2026 and will be submitted for publication in a peer-reviewed journal, and presented at scientific conferences.Trial registration number ISRCTN92928122.